Physical performance profile of handball players is related to playing position and playing class - Krüger, K.; Pilat, C.; Ueckert, K.; Frech, T.; Mooren, F. C. (The Journal of Strength and Conditioning Research, 2014)
The purpose of the study was to compare anthropometric data and physical performance characteristics between different playing positions in professional team handball. Furthermore, a comparison between performance profiles of first and second division players was made. Thirty-four male professional handball players were recruited. Measurement of heart rates (HRs) during official games anthropometric data, sprint ability, jumping performance, throwing velocity, and endurance performance were determined and analyzed with respect to playing position. In a further step, additional 31 players from German second division were recruited to compare their profile on each position with profile of the first division players. Players of wings and backs positions had highest average HRs during game, best times in 30-m sprint tests, best jumping performance, and best anaerobic endurance performance. Similarly, backs and wings reached highest throwing velocities. Regarding anthropometric characteristics, wings were players with lowest body height and weight, whereas pivots were heaviest players and players with highest body mass index (BMI). We further found that wings from first division had a better sprint performance compared with wings from second division. Furthermore, pivots from first division had higher BMI and drop jump performance. Our data demonstrated a close relationship of anthropometric data, physical performance characteristic, and the playing position of handball. These information might be helpful for the assessment and evaluation of talents and may help to develop and optimize position-specific training regimes and identification of talents.